Characterization and application of porous gold nanoparticles as 2‐photon luminescence imaging agents: 20‐fold brighter than gold nanorods. Issue 2 (29th October 2017) - Park, Joo H.; Park, Jisoo; Kim, Suho; Kim, Se‐Hwa; Lee, Tae G.; Lee, Jae Y.; Wi, Jung‐Sub
Abstract : Two‐photon nonlinear microscopy with the aid of plasmonic contrast agents is an attractive bioimaging technique capable of generating high‐resolution images in 3 dimensions and facilitating targeted imaging with deep tissue penetration. In this work, physically synthesized gold nanoparticles containing multiple nanopores are used as 2‐photon contrast agents and are reported to emit a 20‐fold brighter 2‐photon luminescence as compared to typical contrast agents, that is, gold nanorods. A successful application of our porous gold nanoparticles is experimentally demonstrated by in vitro nonlinear optical imaging of adipocytes at subcellular level. Abstract : Gold nanoparticles containing of multiple nanopores could be used as exogenous contrast agents showing a remarkable potential for two‐photon nonlinear microscopy. Pores of a few tens of nanometers scale inside 100‐nm‐sized gold nanoparticles effectively boost light‐absorption and enable an emission of 20‐fold brighter two‐photon luminescence as compared with the typical contrast agents, i.e. gold nanorods.